Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
http://www.journalijar.com/
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty